Influence of low- and high-elevation plant genomes on the regulation of autumn cold acclimation in Abies sachalinensis - Ishizuka, Wataru; Ono, Kiyomi; Hara, Toshihiko; Goto, Susumu (Frontiers in Plant Science, 2015)
Boreal coniferous species with wide geographic distributions show substantial variation in autumn cold acclimation among populations. To determine how this variation is inherited across generations, we conducted a progeny test and examined the development of cold hardening in open-pollinated second-generation (F2) progeny of Abies sachalinensis. The F1 parents had different genetic backgrounds resulting from reciprocal interpopulational crosses between low-elevation (L) and high-elevation (H) populations: L × L, L × H, H × L, and H × H. Paternity analysis of the F2 progeny using molecular genetic markers showed that 91.3% of the fathers were located in surrounding stands of the F1 planting site (i.e., not in the F1 test population). The remaining fathers were assigned to F1 parents of the L × L cross-type. This indicates that the high-elevation genome in the F1 parents was not inherited by the F2 population via pollen flow. The timing of autumn cold acclimation in the F2 progeny depended on the cross-type of the F1 mother. The progeny of H × H mothers showed less damage in freezing tests than the progeny of other cross-types. Statistical modeling supported a linear effect of genome origin. In the best model, variation in freezing damage was explained by the proportion of maternally inherited high-elevation genome. These results suggest that autumn cold acclimation was partly explained by the additive effect of the responsible maternal genome. Thus, the offspring that inherited a greater proportion of the high-elevation genome developed cold hardiness earlier. Genome-based variation in the regulation of autumn cold acclimation matched the local climatic conditions, which may be a key factor in elevation-dependent adaptation.